Self Efficacy dan Social Anxiety pada Mahasiswa Perantauan di Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember - Mawaddah, Iega Nur; Yusuf, David Ilham (Fakultas Dakwah UIN KHAS Jember, 2023)
Anxiety is a state of worry, nervousness or fear, when faced with a difficult situation and thinks something bad will happen to him. Self Efficacy with Social Anxiety are two things that have a mutual relationship, where a belief obtained from previous experiences provides an evaluation of himself in dealing with social situations and performance. Anxiety is also experienced by overseas students of Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember. Based on the survey results, anxiety is a problem for overseas students of Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember. The formulation of the problem in this study is first, how much self efficacy do overseas students of UIN KHAS Jember have? Second, how much social anxiety do overseas students of UIN KHAS Jember have? Third, is there a relationship between self efficacy and social anxiety in overseas students of Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember? The research method used is correlational research. The sampling technique used purposive random sampling with a total sample of 240 samples obtained from questionnaire data, data validity uses validity & reliability tests. The answer to each instrument item uses a Likert scale. The analysis method used is normality test, linearity test, and Pearson correlation test. The first result shows that overseas students of Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember who have moderate self efficacy are more than students who have low self efficacy. Meanwhile, overseas students who have moderate levels of social anxiety are more than overseas students who have low social anxiety. The third result shows a correlation coefficient of -0.259 with sig. 0.000 (p < 0.05), meaning that there is a significant negative relationship between self efficacy and social anxiety in overseas students of Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember.